The impact of risk management implementation on the effectiveness of SAI’s internal audit function - Pradana, Bernardus Dwita; Akbar, Bahrullah; Lukman, Sampara; Kusworo, Kusworo (Badan Pemeriksa Keuangan Republik Indonesia, 2024)
Internal audits play an important role in monitoring the achievement of organizational objectives. However, research on the factors influencing the success of internal audits remains limited. This study aims to investigate the effectiveness of BPK’s Itama (The Inspectorate General of the Audit Board of the Republic of Indonesia) functions, hypothesized to be influenced by risk management policy implementation. This study employs quantitative methods; data were collected via surveys and analyzed using structural equation modeling (SEM) to test theory-based hypotheses. Results reveal a significant positive correlation between risk management policy implementation and the effective functioning of Itama. Additionally, the study identifies key factors determining the success of risk management policy implementation: economic, social, and political conditions. Therefore, internal auditors of supreme audit institutions must consider these external factors when implementing risk management policies. This study contributes to understanding internal audit effectiveness by highlighting the impact of external economic, social, and political conditions.